2023
DOI: 10.3390/agronomy13061534
|View full text |Cite
|
Sign up to set email alerts
|

Optimal Pollution Control and Pump-and-Fertilize Strategies in a Nitro-Polluted Aquifer, Using Genetic Algorithms and Modflow

Yiannis N. Kontos,
Ioakeim Rompis,
Dimitrios Karpouzos

Abstract: Nitro-pollution in a confined aquifer may originate from its recharge area, e.g., agricultural sites, animal feedlots, septic tanks, and other waste disposal sites or from treated wastewater recharge wells. The latter case is studied. Existing water supply pumping wells should be protected for a given period. Instead of typically investigating optimal pump-and-treat or hydrodynamic pollution control management/remediation strategies, a novel combined pollution control and pump-and-fertilize (PAF) approach is p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…Pollution of groundwater due to overextraction, mineral leaching of metal pollutants, excess fertilizer use that penetrates the aquifer, geothermal conditions, and anthropogenic activities is more likely to occur. Furthermore, rivers are exposed over large areas, and pollution may be caused by industrial waste disposal or any other anthropogenic source of pollution [7,50,51]. The results of the present study showed that small dam water quality is excellent and seasonal variations have limited impact on the physic-chemical variations.…”
Section: Discussionmentioning
confidence: 57%
“…Pollution of groundwater due to overextraction, mineral leaching of metal pollutants, excess fertilizer use that penetrates the aquifer, geothermal conditions, and anthropogenic activities is more likely to occur. Furthermore, rivers are exposed over large areas, and pollution may be caused by industrial waste disposal or any other anthropogenic source of pollution [7,50,51]. The results of the present study showed that small dam water quality is excellent and seasonal variations have limited impact on the physic-chemical variations.…”
Section: Discussionmentioning
confidence: 57%